Single-cell profiling of penta- and tetradactyl mouse limb buds identifies mesenchymal progenitors controlling digit numbers and identities - Victorio Palacio; Anna Pancho; Angela Morabito; Jonas Malkmus; Zhisong He; Geoffrey Soussi; Rolf Zeller; Barbara Treutlein; Aimée Zuniga (Nature Communications)
Abstract The cellular interactions controlling digit numbers and identities have remained largely elusive. Here, we leverage the anterior digit and identity loss in Grem1 tetradactyl mouse limb buds to identify early specified limb bud mesenchymal progenitor (LMP) populations whose size and distribution is governed by spatial modulation of BMP activity and SHH signaling. Distal-autopodial LMPs (dLMP) express signature genes required for autopod and digit development, and alterations affecting the dLMP population size prefigure the changes in digit numbers that characterize specific congenital malformations. A second, peripheral LMP (pLMP) population is anteriorly biased and reduction/loss of its asymmetric distribution underlies the loss of middle digit asymmetry and identities in Grem1 tetradactyl and pig limb buds. pLMPs depend on BMP activity, while dLMPs require GREM1-mediated BMP antagonism. Taken together, the spatial alterations in GREM1 antagonism in mouse mutant and evolutionarily diversified pig limb buds tunes BMP activity, which impacts dLMP and pLMP populations in an opposing manner.